2007
DOI: 10.1038/sj.gene.6364438
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a pathogen-response program in peripheral blood cells defines a subgroup of Rheumatoid Arthritis patients

Abstract: Rheumatoid arthritis (RA) is a heterogeneous disease with unknown etiology. Here we aimed to distinguish RA subtypes based on peripheral blood (PB) gene expression profiles in comparison with a pathogen-response transcriptional program. PB was obtained from 35 RA patients and 15 healthy individuals. For expression profiling we used DNA microarrays. A combined cluster analysis of RA and control samples together with samples from a viral infection model revealed that the gene expression profile of a subgroup of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 43 publications
2
30
1
1
Order By: Relevance
“…van der Pouw Kraan et al 40 also reported on a RA subgroup that presented with an interferon type I signature in PBMC, a signature that was previously reported to be a typical molecular characteristic in SLE 41 42. They also described a pathogen-response programme in PBMC reminiscent of that of a poxvirus infection in macaques 43. These observations suggest that different molecular mechanisms may be involved in RA, which may explain other reports and observations, most strikingly the differences in treatment response.…”
Section: Information Generated By Gene Expression Profiling In Ramentioning
confidence: 93%
“…van der Pouw Kraan et al 40 also reported on a RA subgroup that presented with an interferon type I signature in PBMC, a signature that was previously reported to be a typical molecular characteristic in SLE 41 42. They also described a pathogen-response programme in PBMC reminiscent of that of a poxvirus infection in macaques 43. These observations suggest that different molecular mechanisms may be involved in RA, which may explain other reports and observations, most strikingly the differences in treatment response.…”
Section: Information Generated By Gene Expression Profiling In Ramentioning
confidence: 93%
“…Since a quarter of the early arthritis genes overlapped with an influenza-induced gene set it was suggested that the early arthritis signature may partly reflect the response to an unknown infectious agent (Olsen et al, 2004). Accordingly, van der Pouw Kraan and colleagues observed similarity with a common virus response signature in a subset of RA patients (van der Pouw Kraan et al, 2008). Not surprisingly, the majority of these patients had an activated IFN-response program.…”
Section: Genes and Signatures Involved In Early Vs Late Ramentioning
confidence: 98%
“…Moreover, the immune defense gene program that was activated in the subgroup of RA patients was reminiscent to that of virus-infected macaques (van der Pouw Kraan et al, 2008). Comparative analysis between paired tissue and peripheral blood profile revealed that there exists no concordance in the presence of IFN-response activity between the two compartments (van Baarsen et al, 2010a)…”
Section: A Type I Ifn Response Signature In the Peripheral Blood Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…При этом больные РА с более высокими уровнями синовиального воспаления и экспрессии TNFa в синовии [18], а также при увеличении экспрессии генов бета-рецептора IL2, SH2 домена 2А и GOS2 в периферической крови более чувствительны к блокаде TNFa [19]. Более того, высокая базальная экспрессия TNFa у больных, у которых концентрация С-реактивного белка (СРБ) в крови после терапии уменьшалась до уровня, наблюдаемого у здоровых лиц, оказалась маркером эффективности терапии ингибитором TNFa, инфликсимабом [20].…”
Section: экспрессия фактора некроза опухолей альфа и интерферонов 1 тunclassified